(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2019)
For Muslims, the formation of the family begins with choosing a life partner, based on certain criteria provided in Islam. One of the efforts to prevent marital conflict is to examine the practice of kufu (equivalence) between the future husband and wife before getting married. This article analyses the concept of kufu as practised among in Brunei Darussalam, and its relation with the family institution nowadays. A structured interview was carried out with eight authoritative informants from the Shariah Court and Family Counselling Service Division of the Shariah Affairs Department of Brunei. Using ATLAS.ti, a computer program, a descriptive analysis was made based on the data collected. The study found that the term kufu is not well-known among the people of Brunei and the Muara District. Due to this, they are less aware of the importance of kufu in producing better-quality families. Keywords: life-partner selection, kufu, family institution, marital conflict